Proceedings of the 9th International Conference for Science Educators and Teachers (ICSET 2017) 2017
DOI: 10.2991/icset-17.2017.126
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Guidance and Counseling Efforts to Prevent Cheating Behavior

Abstract: Academic dishonesty or cheating is behaviour that is done by the students, they have become a serious problem in the world. One of the functions of guidance and counselling teacher is to prevent the occurance of bad behaviour. So, guidance and counselling teachers should strive to prevent cheating behaviour. The purpose of this study is to describe teacher guidance and counselling efforts in preventing cheating behaviour, and to examine whether there are differences in the efforts of guidance and counselling t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
(8 reference statements)
0
5
0
1
Order By: Relevance
“…Research on application of counselling therapies to curb incidences of academic dishonesty as a preventive approach indicates significant results. For instance, Ahmad (2017) found that guidance and counselling efforts of teachers could result in preventing cheating behaviour among students. Moreover, Mckenzie, Murray K., Murray A. and Richelieu (2015); Wijayanti, Sugiharto and Wibowo (2019) in their respective studies found that counselling services and therapies are very effective in the treatment of students against academic dishonesty.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Research on application of counselling therapies to curb incidences of academic dishonesty as a preventive approach indicates significant results. For instance, Ahmad (2017) found that guidance and counselling efforts of teachers could result in preventing cheating behaviour among students. Moreover, Mckenzie, Murray K., Murray A. and Richelieu (2015); Wijayanti, Sugiharto and Wibowo (2019) in their respective studies found that counselling services and therapies are very effective in the treatment of students against academic dishonesty.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…School counselors need to increase students understanding of the risks of online game addiction through several guidance and counseling services to prevent students addicted to online games. One of the functions of guidance and counseling services in schools is to prevent students from behaving improperly (Ahmad, 2013;2017;Prayitno & Amti, 2004). Because, bad behavior displayed by students in schools will disrupt the teaching and learning process which will have an impact on student learning outcomes (Yunika, Alizamar, & Sukmawati, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a lack of guidance contributes to people cheating. When individuals lack proper guidance, such as parental support or mentorship, they may be more inclined to engage in unethical activities or fail to comprehend the gravity of their actions (Ahmad, 2017).…”
Section: Demography Informationmentioning
confidence: 99%